(untitled) (The Peerian Journal, 2022)
In the work, the results of the analysis of spring, karst and underground urban waters in the determination of potassium, calcium, magnesium, sodium, phosphorus, sulfur, iron, chlorides, iodides and fluorides, as well as the influence of these components on human health, were evaluated by chemical and physico-chemical methods of analysis